Sanksi Pidana bagi Pelaku Tindak Pidana Pedofilia terhadap Anak - Agus Rai Mahardika; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2020)
In Indonesia, to date, the world of children has become very concerning. This is not in words, but there is a fact that does exist and should receive serious attention. This is evidenced by the growing number of non-governmental organizations caring about the fate of Indonesian children, and there is good faith in the government to overcome the situation by issuing stricter rules and regulations to ensure the protection for children. This study examines the legal arrangements for perpetrators of criminal acts of sexual harassment against minors and the legal sanctions. This research is a legal research and the approach used is a normative juridical approach that is descriptive analytic. The data collected comes from the prevailing laws and regulations, which are analyzed quantitatively and then interpreted by deductive method. Sexual harassment appears as a form of sexual act or discourse in which an adult seeks sexual gratification with a minor. Sexual abuse of a child can include contact or interaction between a child and an adult, wherein the child is exploited for sexual stimulation by the offender or another person who is in a position of power or control over the victim, including inappropriate physical contact, making pornography or showing adult genitals to children. Sanctions for sexual harassment are strictly regulated in the Criminal Code, namely in Articles 287, 290, 293, 294, and 295. Meanwhile, according to the Child Protection Law no. 23 of 2002, it is regulated in articles 78, 82 and 88. In all of these articles, it is explained about the criminal provisions and the types of sanctions given to the perpetrators of the sexual harassment. The sanctions given are in the form of imprisonment and fines.